polymorphism in PTPN2 gene is associated with an earlier onset of type 1 diabetes - Espino-Paisan, Laura; de la Calle, Hermenegildo; Fernández-Arquero, Miguel; Figueredo, Maria Ángeles; de la Concha, Emilio G; Urcelay, Elena; Santiago, Jose Luis (Immunogenetics (New York), 2011)
The Wellcome Trust Case Control Consortium (WTCCC) genome-wide study found association of PTPN2 with three autoimmune diseases, among them is type 1 diabetes (T1D). This result was confirmed by a follow-up study that pointed to new independent signals within the region. However, both studies were performed in patients with an early-onset T1D. We aimed at replicating the previous results and studying the influence of these polymorphisms in the age at T1D debut. We genotyped 439 T1D Spanish subjects (age at onset, 1 to 65 years) and 861 controls for two PTPN2 single nucleotide polymorphisms (SNPs), rs2542151 and rs478582, and studied the effect of both polymorphisms in age at onset through stratified and continuous analyses. The frequency of rs2542151*G carriers was significantly higher in the early-onset group compared with late-onset patients (p = 0.023) and with controls (OR = 1.61 [1.14-2.26]; p = 0.005). No significant differences were found between controls and late-onset patients. The log-rank chi-square test for the Kaplan-Meier plots (carriers of susceptibility allele vs non carriers) was statistically significant (χ ₁df ² = 4.485; p = 0.034), yielding an earlier disease debut for G carriers. The analysis of the SNP rs478582 did not reach statistical significance. In summary, we replicate the association detected by the WTCCC and propose that the rs2542151*G allele confers risk to an earlier onset of T1D.